David Y.H. Yu and Sidney C.H. Cheung, eds.: The Globalization of Chinese Food - Davidson, Alan (Petits Propos Culinaires, 2024)
David Y.H. Yu and Sidney C.H. Cheung, eds.: The Globalization of Chinese Food: Curzon, 2002: ISBN 0-7007-1403-0: 196 pp., h/b, £45.